Factors Associated with Decreasing Incidence of Stunting in the Working Area of the Palu Health Center - Marselina Palinggi; Muh. Jusman Rau; Nur Hikma Buchair; Annisa Raudhatul Jannah; Rahmania; Moh. Fikram Dg Sirata (Media Publikasi Cendekia Indonesia, 2023)
Stunting in toddlers needs special attention because it can hamper children's physical and mental development. Based on a report from the Palu City Health Office in 2021, the number of stunted toddlers reached 8.00%. This study aimed to determine the factors associated with a decrease in the incidence of stunting in the working area of the Palu City Health Center (Puskesmas). This type of research was quantitative observational analytic with a cross-sectional study design. The population in this study were all mothers registered in the working area of the Pantoloan Health Center, Nosarara Health Center, and Tipo Health Center with an eligible sampling technique, then the sample in this study was 98 samples. Data was collected based on a questionnaire that would be analyzed using univariate and bivariate analysis. This study's results indicated no relationship between the variable provision of basic immunization (p=0.906) to a decrease in the incidence of stunting in the working area of the Palu City Public Health Center. A relationship was identified between the time variable providing weaning food (p=0.039) and decreased stunting in the Public Health Center Palu City working area. There was a relationship between the variable support of health workers (p=0.012) to a decrease in the incidence of stunting in the working area of the Palu City Health Center. Strengthening health promotion performance in developing promotive and preventive programs is recommended, particularly in improving complete basic immunization programs